Restructuring the Nigerian economy the place of privatisation papers and proceeedings of a national seminar on privatisation (Securities Exchange Commission, 1986)
The book is divided into three section thus section 1 covers the opening ceremonies and consists of welcome address by Alhaji A.O.G. Otiti, Chairman, Securities and Exchange Commission and Deputy Governor, Central Bank of Nigeria.
osa 16/4/19
Loans
Keywords: Economy; Nigeria